2000
DOI: 10.1161/01.res.86.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Redox Changes of Cultured Endothelial Cells and Actin Dynamics

Abstract: Abstract-We studied the association between the production of reactive oxygen species, actin organization, and cellular motility. We have used an endothelial cell monolayer-wounding assay to demonstrate that the cells at the margin of the wound thus created produced significantly more free radicals than did cells in distant rows. The rate of incorporation of actin monomers into filaments was fastest at the wound margin, where heightened production of free radicals was detected. We have tested the effect of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 43 publications
12
141
0
1
Order By: Relevance
“…Crawford et al (1996) demonstrated actin polymerization was concurrent with increased superoxide production in post-hypoxic endothelial cells. Moreover, endothelial cell migration in the wound was signi®cantly retarded in the presence of DPI or MnSOD mimetic (Moldovan et al, 2000). Activation of Rac has been shown to participate in actin polymerization and cell proliferation, suggesting that Rac-mediated superoxide production may contribute, at least partially, to cell proliferation and migration (Qiu et al, 1995;Joneson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Crawford et al (1996) demonstrated actin polymerization was concurrent with increased superoxide production in post-hypoxic endothelial cells. Moreover, endothelial cell migration in the wound was signi®cantly retarded in the presence of DPI or MnSOD mimetic (Moldovan et al, 2000). Activation of Rac has been shown to participate in actin polymerization and cell proliferation, suggesting that Rac-mediated superoxide production may contribute, at least partially, to cell proliferation and migration (Qiu et al, 1995;Joneson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro wound models in cultured airway epithelial systems, DUOX1 was found to play a critical role in cell migration as part of the wound repair response (87,108), illustrating an additional function of DUOX1 in maintenance of epithelial integrity. This is not a unique property of DUOX1, as other NOX isoforms have also been linked to proliferation and/or migration in various other cell types (70,71,116,117), pointing to a possible common mechanism by which NOX/DUOX activation promotes these processes.…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%
“…Additionally, NOX-mediated effects on e.g. cell proliferation or migration also depend on strict spatial localization of NOX activation in association with the cytoskeleton (70,71) or in membrane rafts (43,72,73), and on direct interactions with target proteins (3,43,55). This allows for effective oxidative signaling in the presence of abundant cytosolic antioxidant mechanisms (Cu/Zn SOD, GSH peroxidase), and assures confined oxidant production and target specificity.…”
Section: Location Mattersmentioning
confidence: 99%
“…89 ROS in turn increases vascular permeability by actin reorganization or by inactivating junction-associated phosphatases. 90,91 Moreover, VEGFinduced Rac1 activation has been demonstrated to be regulated by the GEF Vav2, leading to generation of ROS and VE-cadherin internalization. 25,92,93 We recently showed that the multi-domain GEF Trio interacts with VE-cadherin.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%